STUDI EKSPLORATIF TENTANG KOMPETENSI DIGITAL GURU DALAM PEMANFAATAN PLATFORM PEMBELAJARAN DIGITAL DI SEKOLAH DASAR - Sasabillah; Hariandi, Ahmad; Zahyuni, Violita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology requires teachers to have strong digital competencies to support an effective, creative, and adaptive learning process. This study aims to describe the digital competence of elementary school teachers in utilizing digital learning platforms and the factors that influence them. This research uses a qualitative approach with a case study design carried out at SDN 13/1 Muara Bulian, Batanghari Regency, Jambi Province. Data were collected through observation, interviews, and documentation of teachers in grades IV, V, and VI. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results show that teachers have basic digital literacy skills and have utilized platforms such as Google Classroom, YouTube, Canva, WhatsApp, and Quizizz for learning activities. However, limited infrastructure, internet access, and lack of digital training are the main obstacles. Teachers' digital competencies are influenced by individual factors, motivation, institutional support, and technology availability. These findings affirm the importance of strengthening digital literacy and continuous training to improve teacher professionalism in implementing technology-based learning in the digital era.